1990
DOI: 10.1007/bf03349530
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid dysfunction in a prospectively followed series of patients with progressive systemic sclerosis

Abstract: Thirty-nine patients with progressive systemic sclerosis (PSS) in stable clinical conditions were extensively evaluated for the presence of thyroid disease. Two patients had previously undetected hypothyroidism while 7 additional patients had normal serum thyroid hormone levels but an exaggerated TSH response to thyrotropin-releasing hormone (TRH) administration, consistent with subclinical hypothyroidism. Four of the 9 subjects with abnormal TRH responses had positive antithyroid antibodies and of the remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 32 publications
5
13
1
Order By: Relevance
“…This indicates that the control was not biased towards a lower hypothyroidsm prevalence in comparison with the general population and that the current results agree closely with those reported by a population-based survey so far in the literature (35), which showed a 8% prevalence for subclinical hypothyroidism in females over the age of 40 years (36). Interestingly, mean TSH value was significantly higher in SSc than in controls, in agreement with other studies (10,12,13). Autoimmune phenomena are an almost constant feature of patients with SSc (1-6).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This indicates that the control was not biased towards a lower hypothyroidsm prevalence in comparison with the general population and that the current results agree closely with those reported by a population-based survey so far in the literature (35), which showed a 8% prevalence for subclinical hypothyroidism in females over the age of 40 years (36). Interestingly, mean TSH value was significantly higher in SSc than in controls, in agreement with other studies (10,12,13). Autoimmune phenomena are an almost constant feature of patients with SSc (1-6).…”
Section: Discussionsupporting
confidence: 81%
“…Population studies have shown the prevalence of AbTPO to be around 10% in females (range 10-15%), and it increases with age (from 8% in females over 18 years of age to about 30% in women over 70) (35,36). In our female controls, the prevalence of AbTPO positivity was 19%, similar or higher than that reported in some studies in SSc (18-19%) (12,14) and fully in the range of the reported ageadjusted prevalence rates for the Italian population (29,34) and for other population-based surveys (35,36). In female SSc the prevalence of AbTPO positivity was 39%, significantly higher.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…SSc patients showed a higher odds ratio for the presence of antithyroid antibodies. According to the literature, the percentage of antithyroid antibodies in SSc ranges from 12 to 52% [36][37][38][39][40][41] and the percentage of hypothyroidism from 2.4 to 26%. 38,42 A previous study showed that presence of hypothyroidism in SSc patients was associated with higher prevalence of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%